Knowledge of Cardiovascular Emergency Management Among Posbindu Cadres - Tiara Margaretha Putri Fauzi Tiara Margaretha Putri Fauzi; Mohamad Miftachul Ulum Mohamad Miftachul Ulum; Andi Hayyun Abiddin (JOSAR (Journal of Students Academic Research), 2026)
Non-communicable diseases (NCDs) are becoming an increasingly troubling health problem, every year, the number of cases continues to increase, causing deep concern, especially those related to the cardiovascular system remains the leading cause of death and remains top-ranked in East Java. Posbindu cadres have a very important role in PTM cardiovascular emergencies. The purpose of the study was to determine the level of knowledge of cardiovascular emergencies in posbindu cadres. The method that has been used in this study is descriptive quantitative, with a total of 30 respondents taken with a total sampling technique. Data collection instruments in the form of questionnaire sheets containing knowledge of cardiovascular emergencies. Based on research conducted in March 2024 at Posbindu 2 Pakunden Village, Blitar City. The results of this study showed that the level of knowledge of cardiovascular emergencies in posbindu cadres was mostly good knowledge. Knowledge in cardiovascular emergencies that is still lacking is about cardiovascular risk factors. The lack of action in conveying information and the internet causes most respondents to lack understanding and has never been done such as education or training so they cannot implement it.